In Silico Evaluation of Black Cumin Oil Constituents for Selective Anti-Inflammatory Inhibitor of COX-2 And 5-LOX - Syarifatul Mufidah; Putri Rachma Novitasari; Prita Anggraini Kartika Sari; Hani Badriyah Hidayati (Indonesian Journal of Pharmacy and Natural Product, 2025)
Black cumin oil (Nigella sativa) is widely known for its anti-inflammatory properties, attributed to various bioactive compounds. This study aimed to evaluate the binding affinity and selectivity of five major compounds from black cumin oil: dithymoquinone, thymoquinone, thymohydroquinone, p-cymene, and thymol, against key inflammatory enzymes: COX-1, COX-2, and 5-LOX, using an in silico approach. All compounds were assessed for drug-likeness using Lipinski’s Rule of Five before molecular docking with AutoDock Vina. Celecoxib, a selective COX-2 inhibitor, was used as a reference compound. Dithymoquinone demonstrated strong binding affinity to COX-2 (-9.3 kcal/mol) and 5-LOX (-8.4 kcal/mol), comparable to celecoxib (-9.9 and -8.3 kcal/mol, respectively), while showing lower affinity for COX-1 (-7.5 kcal/mol). The interaction analysis revealed hydrogen bonds and van der Waals forces with several active site residues, suggesting a stable and selective interaction. Other compounds showed moderate to high affinity but lacked the same degree of selectivity due to their interaction with COX-1. These findings indicate that dithymoquinone has the potential to act as a selective anti-inflammatory agent with a reduced risk of gastrointestinal side effects commonly associated with non-selective NSAIDs. The results support further investigation of dithymoquinone in preclinical and clinical settings to validate its efficacy and safety.